Implementation of a Multisite Financial Reimbursement Program in Cancer Clinical Trials Integrated With Patient Navigation: A Pilot Randomized Clinical Trial. Issue 6 (23rd June 2022) - Borno, Hala T.; Zhang, Li; Zhang, Sylvia; Lin, Tracy K.; Skafel, Andrea; Nieves, Elena; Dornsife, Dana; Johnson, Robert; Rhoads, Kim; Small, Eric; Spicer, Darcy
Abstract : PURPOSE: Cancer clinical trial participants face considerable indirect costs associated with participation, such as travel and lodging, which may contribute to poor enrollment. Here, we report the findings in IMproving Patient Access to Cancer clinical Trials, a pilot feasibility study investigating the efficacy of offering a financial reimbursement program (FRP) during a therapeutic clinical trial discussion with or without additional outreach in improving patient enrollment. METHODS: Study participants for this study were recruited at two National Cancer Institute–designated comprehensive cancer centers (CCCs) from April 8, 2019, to September 19, 2019. Eligible participants were adults with a cancer diagnosis being approached to consider enrollment in a clinical trial. Participants were randomly assigned 1:1 to receive no follow-up (usual care) or a follow-up telephone call to facilitate FRP utilization stratified by study site. The target enrollment was 132 patients, with 66 patients in each study arm. The primary outcome was the consent rate to the multisite interventional study on the FRP among participants enrolling in clinical trials. RESULTS: The study had a 78% consent rate and enrolled a total of 132 participants, of whom 51% were non-White compared with 28% of CCC treatment clinical trial participants in 2019. No difference in enrollment in clinical trials between the two study arms was observed as the proportion of enrollment was 70% for both study arms. The most common reason for not enrolling in a clinical trial was due to ineligibility determined through screening procedures (75%). CONCLUSION: The current study observed that implementation of FRP at CCCs is feasible and serves a diverse patient population. Future studies will measure the impact of programs on overall clinical trial accrual and among racial/ethnic minorities.